The study of formation damage by custom fabricated rig - Ismail, Issham; Teow, Andrew Ket Seang (SPE-UTM Skudai, 2002)
This paper introduces a rig that enables the formation damage studies to be conducted at near downhole condition in the laboratory. The rig was equipped with many special features such as shuttle sleeve, multi angle rotating rig, and sensing devices. A drill pipe was installed in the testing unit in order to simulate the drilling operation. Thus, the introduction and integration of these features enable various forms of formation damage studies to be carried out under static and dynamic conditions. The custom fabricated rig has the potential to assist oil companies in their formation damage studies. It also provides an opportunity to the service companies to evaluate the performance their mud additives or based oil without risking the wells.